Memorandum of Understanding for Hosting of Nagasaki University Master Course Students between the School of Public Health, BRAC University, Bangladesh and Graduate School of International Health Development, Nagasaki University, Japan - School of Public Health, BRAC University; Graduate School of International Health Development, Nagasaki University (School of Public Health, BRAC University and Graduate School of lnternational Health Development, Nagasaki University, 2013)
The School of Public Health, BRAC (Bangladesh Rural Advancement committee) University, Dhaka, Bangladesh and the Graduate school of International Health Development, Nagasaki University, Nagasaki, Japan, based on Clause 3 of the "Agreement on Academic Cooperation" between BRAC University and Nagasaki University dated May 30, 2008, have agreed to conclude this memorandum in order to confirm and set forth the details of collaborative research, education and capacity building.